Perancangan Animasi 2D “Robek” Sebagai Media Edukasi Tentang Bakat dan Minat Anak - Afif, Riky Taufik; Nuruddin, Muhammad Ihsan; Sumarlin, Rully (Institut Seni Indonesia Yogyakarta, 2025)
An important aspect of every person's life is talent and interest. They not only determine what makes a person unique, but also play an important role in personal development, success, and happiness. If someone lives life according to their interests and talents, they tend to be happier and more fulfilled, and this can help them live a better life overall. If someone has strong talents and interests, then that person can choose the educational program or major that best suits their interests. When we can choose or determine a field that suits our talents and interests, our chances of success in that field are very high. Therefore, this research will discuss the importance of talent and interest in children. In this research the author used qualitative methods. Seeing the many phenomena of majors at college level, it turns out that students are confused about their choices, many of them follow their friends' choices or even their parents' choices. This 2D animation